Some questions regarding freedom from self-disclosure as one of the principles of the criminal procedure - Dekailo, Petro; Babiy, Volodymyr (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
One of the principles of criminal proceedings - freedom from self-incrimination and the right not to testify against close relatives and family members - is analyzed in detail. The main disadvantages of its use directly in practice have been identified. The opinions of numerous scientists, the practice of the ECtHR and the experience of foreign countries regarding the application of the above-mentioned principles of the criminal procedural legislation of Ukraine were considered. Based on this, a number of proposals for improving the effective use of this principle are highlighted.It is worth noting that the entire criminal process must be carried out in compliance with all 22 principles provided for by the Criminal Procedure Code of Ukraine. Any procedural actions committed in violation or non-compliance with at least one of them becomes illegal. That is why it is extremely important for all participants in criminal proceedings to understand in detail, and most importantly, the meaning and essence of each of these principles, without exception. Because it depends on the observance of human rights, the establishment of justice and, above all, the decision of people's fate. A detailed explanation of each of the principles, the search for ways to improve, the elimination of conflicts in the current legislation and the exclusion of the possibility of abusing the rights arising from these principles are no less important than their observance in criminal proceedings.